2015
DOI: 10.1108/jmhtep-04-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing teaching relationships through therapeutic use of self

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…This means that teachers oftentimes communicate with their students, friends, and colleagues about their personal concerns and matters and express their feelings to their principal without hesitation. This is congruent with the idea of Williams (2015) [51] which stressed that teacher self-disclosure is an important tool to develop trust and confidence among learners. Similarly, the study of Song et al (2016) [45] revealed that the mutual relationship between student and teacher was increased through teacher self-disclosure which eventually leads to a more productive learning environment and improved class satisfaction.…”
Section: Personal Effectiveness Of Junior High School Teacher In Davasupporting
confidence: 82%
“…This means that teachers oftentimes communicate with their students, friends, and colleagues about their personal concerns and matters and express their feelings to their principal without hesitation. This is congruent with the idea of Williams (2015) [51] which stressed that teacher self-disclosure is an important tool to develop trust and confidence among learners. Similarly, the study of Song et al (2016) [45] revealed that the mutual relationship between student and teacher was increased through teacher self-disclosure which eventually leads to a more productive learning environment and improved class satisfaction.…”
Section: Personal Effectiveness Of Junior High School Teacher In Davasupporting
confidence: 82%